Toxoplasmosis vaccines: what we have and where to go? - Yizhuo Zhang; Dan Li; Shaohong Lu; Bin Zheng (npj Vaccines, 2022)
Abstract Despite recent major advances in developing effective vaccines against toxoplasmosis, finding new protective vaccination strategies remains a challenging and elusive goal as it is critical to prevent the disease. Over the past few years, various experimental approaches have shown that developing an effective vaccine against T. gondii is achievable. However, more remains unknown due to its complicated life cycle, difficulties in clinical translation, and lack of a standardized platform. This minireview summarizes the recent advances in the development of T. gondii vaccines and the main obstacles to developing a safe, effective and durable T. gondii vaccine. The successes and failures in developing and testing vaccine candidates for the T. gondii vaccine are also discussed, which may facilitate the future development of T. gondii vaccines.